FUSD Board Candidate Jerry McMenamin and Friends Election Night at Mama Luz's - Watkins, Howard::::::::: (1989)
Guest speaker Temple Beth Israel Rabbi Kenneth Segel with dressed up Robin Watkins and ? with Bill Fischer